پاکستان میں سیاسی ومعاشرتی بد امنی: سیرت نبوی کی روشنی میں حلThe Solution of Political and Social Instability in Pakistan in the light of Sirah of the Prophet (Al-Qamar, 2021)
This article mentions some of the responsibilities of the leaders which are the most important responsibilities of the Islamic government, such as: implementation of Sharia, establishment of justice and justice, commanding the good and forbidding the evil, establishing peace, reforming the society, etc. Pakistan has a democratic system of government which is a secular system in which the concept of accountability before God is missing. Rather, they are obtained through rank and proper tagodo and are considered a sign of honor and dignity. Therefore, everyone tries to take over the government in legitimate and illegitimate ways. Dictators, tyrants and dictators are sovereign. Their lavish pomp is enough to show how fearless and irresponsible they are They are rich people, the stars of their soul have made the life of the people indigestible. but if today's age is compared to the early period of Islam, then it is clear that the righteous servants of God have always been running away from positions and responsibilities and if any such burden has been placed on them against their will. So his whole life was buried under this burden. They carried out their responsibilities with such zeal and dedication that it is difficult to find an example in history. The Islamic State is an ideological state whose goal is the individual and collective well-being of the people. This well-being extends not only to worldly goods but also to the welfare of the Hereafter. Achieving contentment, protecting their lives, protecting them from oppression and tyranny, imitating Islamic rules in all actions and spheres of the state and making it necessary to preach Islamic call all over the world are among its main objectives. The first duty of the ruler and his government in the Islamic State was to establish the Islamic way of life without any change and to promote the good in accordance with the moral standards of Islam and to eradicate the evil. And this is the purpose of the Muslim Ummah according to the Qur'an. The successful progress of the Islamic Da'wah depends largely on its leadership. if he is God-fearing, responsible, insightful, courageous, self-sacrificing and of ideal character, then the morale of his comrades behind him and the morale of his enemies will be low. Leaders sincerely believe in the principles on which the Islamic system is based. The people in charge of leadership should be God-fearing, virtuous and honest.
Keywords: Leaders; government; Sharia; justice; democratic system; secular system; Dictators; leadership; Muslim Ummah